Top managers in the digital age: Exploring the role and practices of top managers in firms' digital transformation - Michaela Wrede; Vivek K. Velamuri; Tobias Dauth (Managerial and Decision Economics, 2020)
This study explores the role and facilitating actions of top managers in response to the digital transformation. Building on 27 in-depth interviews with top managers and close associates from large German firms, we find that top managers respond to the digital transformation by engaging in three key actions: understanding digitalization, setting the formal context for digitalization, and leading change. Moreover, findings emphasize that top management team support is essential in firms' digital transformation. Overall, this study contributes novel insights about the consequences of top managers for firms and establishes an initial foundation for investigating top managers in the digital age.
Keywords: 650